Perancangan Website Informasi Akademik Untuk TK Islam Birrul Walidayn Menggunakan Metode Agile - Ardi Maulana; Muhamad Evan Raesandi; Muhammad Microsort Ramadhan; Saprudin (CV. Multi Kreasi Media, 2025)
The rapid development of information technology is driving the education sector to undergo digital transformation in order to improve the efficiency of information delivery. At TK Islam Birrul Walidayn, the communication system that still relies on blackboards and direct interactions between teachers and parents has proven to be impractical and often slows down the flow of information. In response to this, an academic website was designed with the aim of accelerating, streamlining, and organizing the process of information distribution between the school and parents. The development of this system uses an Agile approach, which allows the development process to be carried out iteratively and responsively to user needs. Each stage in the development cycle—from the planning stage to evaluation—is repeated to ensure the final result meets expectations. The website developed in this internship activity is designed to display student data, activity schedules, important announcements, and real-time child development reports. With the presence of this digital platform, the management of academic information becomes more efficient, while also making it easier for parents to monitor their children's activities and growth anytime and anywhere.